Toughening Financial Sanctions on Russia: Enforcing Energy Sanctions and Reducing Shadow Reserves Effectively - Benjamin Hilgenstock; Elina Ribakova; Guntram B. Wolff (Intereconomics, 2023)
Financial sanctions are key in enforcing restrictions on Russian energy exports - in particular the G7/EU oil price cap regime - due to financial institutions' critical role in cross-border transactions. While the energy sanctions regime is having an impact on export earnings and budget revenues, evidence for potentially widespread violations is also emerging. Moreover, favourable external dynamics have allowed Russia to accumulate substantial assets abroad, "shadow reserves", which need to be kept out of reach of the regime. To address this, a number of steps could be taken, including tasking central banks and supervisory authorities with the identification of Russian foreign assets to ensure that funds cannot be used to widen monetary and fiscal policy space, and addressing loopholes in the sanctions regime.
Keywords: F5; B17; 330